Kvintilianas apie iškalbos privalumus - Valienė, Rasa (Literatūra, 2007)
In the Institutio Oratoria of Quintilian we find a presentation of a theory of the virtues of eloquence: purity of language (latinitas), clarity (perspicuitas), appropriateness (aptum) and ornament (ornatus). All of them were originated by earlier Greek philosophers Aristotle and Theophrastus. Later this theory was taken on and elaborated by Roman rhetoricians – Cicero and Quintilian. Aristotle in his Rhetoric explicitly identified three of the four virtues (clarity, appropriateness and correctness). Theophrastus created a theory of four virtues of eloquence (correctness, clarity, appropriateness and ornament). His system was adopted by most of others. Dionysius, however, developed the most complex system of virtues. He presented a theory of virtues, which were divided into necessary (purity of language, appropriateness, lucidity and brevity) and accessory ones. The accessory virtues were further subdivided into another three groups. Rhetorica ad Herennium offered a three fold system: elegantia (including both correctness and clarity), compositio (similar to appropriateness) and diginitas (similar to ornament). Basically, in almost all aspects being closer to Cicero (who continues the tradition of Theophrastus), Quintilian is more focused on his theory of eloquence. He discusses the virtues of eloquence very widely and deeply, step by step, drawing a number of examples and including the educational process of an orator. Above all, although the theory of four virtues of Quintilian has been influenced by Ciceron, to some extent in general it does not claim originality and plays a paramount role in modern rhetorics, stylistic and pedagogy.